Specificity of psychological readiness for changes and psychological resilience in the employees of the State Criminal-Executive Service of Ukraine - O. V. Mitroshkina (Law and Safety)
The work focuses on the study of psychological readiness for change and psychological resilience among employees of the State Criminal-Executive Service of Ukraine. It is shown that in the conditions of reforming, readiness for changes is a psychological condition for successful professional activity and personal self-realization of the staff of the criminal executive service. The content of the concept of “psychological readiness” and “psychological readiness for change” is disclosed, the purposefulness of the study of psychological resilience as one of the factors of psychological readiness for change is substantiated. The purpose of the study was to identify the features of the functioning of psychological readiness for changes in the context of psychological resilience of employees of the State Criminal-Executive Service of Ukraine.